Factors associated with psychological distress, fear, and coping strategies during coronavirus disease 2019 pandemic among community members in Nepal - Oli, Natalia; Bhattarai, Nikita; Shrestha, Santripti; Rahman, Muhammad Aziz (Journal of Kathmandu Medical College, 2023)
Background: Coronavirus disease 2019 (COVID-19) pandemic had huge impact on social, psychological, and economic well-being of general community people in Nepal. Objectives: To assess the extent of psychological distress, fear, and level of coping strategies among community members in Nepal. Methods: A nationwide analytical cross-sectional study was conducted among Nepali residents aged >=18 years using an online structured questionnaire during 2020 December to 2021 January. Kessler Psychological Distress Scale (K10), Fear of COVID-19 scale (FCV-19S) and Brief Resilient Coping Scale (BRCS) were used in this study. Univariate and multivariate logistic regression analyses were conducted to adjust for potential confounders. Ethical clearance was obtained from institutional review committee of Kathmandu Medical College. Results: Among 311 respondents, 167 (53.7%) were female. Median age (IQR) 31.3 (13) years with age range 18-69 years. Mean age was 31.4 ± 10.3 years. Being above 30 years old (AOR 3.8, 95% CI 2.13-6.84) were associated with higher levels of psychological distress. Being a female (AOR 0.55, CI 95% 0.30-0.99), moderately improved working situation due to change of employment (AOR 0.39, CI 95% 0.20-0.76), having little perceived distress due to change of employment status (AOR 0.52, 95% CI 0.27-0.97), having positive impact of COVID-19 on financial situation (AOR 0.28, 95% CI 0.13-0.61) were associated with lower levels of fear based on the FCV-19S scale. Conclusions: This study identified individuals who were at higher risk of psychological distress, level of fear, and low coping strategies during COVID-19 pandemic in Nepal. These findings would assist in exploring the strategies to support mental health of vulnerable population during pandemic and post-pandemic periods.